The effect of Bean type and mass on the reproduction of Callosobruchus maculatus - Brezina, Caleb; Spiesman, Brian (My University, 2018)
This research project is involved in the ecological aspect of resource partitioning. This is important in the reproductive capacity of the bean beetle. (Mitchell, 1975). In order to test this reproductive capacity, an experiment with the host beans has been set up. The question is whether the reproductive capacity is more affected by the type or amount of beans. Since adults do not require food, eggs were counted after the adults died. (Blumer and Beck, 2018). It was found that the adults preferred the mung beans. There was also no relevance between mass and the amount of eggs. These ecological findings show that it is not necessarily the mass of the beans that matters. It is in fact the type that the beetle prefers. (Gerson and Applebaum, 2014).
Keywords: Fall 2018